New species of Haematoloechus (Digenea: Plagiorchidae) in the lung of the foothill yellow-legged frog Rana boylii (Anura), from Humboldt County, California, USA - David Zamparo; Amanda Ferrao; Daniel R. Brooks; Jamie Bettaso; Rosario Mata-López (Revista Mexicana de Biodiversidad)
A new species of Haematoloechus is described from the lungs of Rana boylii from Humboldt County, California. The new species is similar to Haematoloechus buttensis, Haematoloechus kernensis, and Haematoloechus complexus in general course of the uterus and gonad shape. It is similar to H. buttensis by having a cirrus sac terminating midway between the posterior margin of the pharynx and the anterior margin of the ovary, and having a smaller oral/ ventral sucker ratio; to H. complexus by having the genital pore ventral to the pharynx, and it is similar to H. kernensis by having a larger oral sucker to pharynx width ratio. The new species is unique by lacking an extra-cecal longitudinal uterine loop from the hind-body. Molecularly, the new species differs 1.04–1.15% in partial 28S sequence with respect to H. complexus, and a monophyletic grouping of these specimens in a phylogenetic analysis of all available sequence data consistent with the species-specific status proposed herein. Evidence is also presented to suggest that specimens identified as H. buttensis in Rana pretiosa from British Columbia, Canada represents a new, but still undescribed species. The importance of conducting biological inventories of helminths, along with continued monitoring of populations, and collections based taxonomy are related.